COVID-19 Impact Monitoring at the Household Level : Burkina Faso, Brief No. 7 - Tsimpo Nkengne, Clarence (World Bank, Washington, DC, 2021)
This note presents the results of the seventh round of a nationally representative telephone survey (HFPS). The BFA Covid-19 (coronavirus) HFPS - Round 7 was administered between February 12 and March 2, 2021. The following modules were administered during the 7th visit: Access to basic services; Employment and income; Food Safety; Mental health, and Social protection. In addition to the 1985 households successfully interviewed in the sixth round, in an effort to maintain sample size, additional 47 households that had not been successfully interviewed in previous rounds but did not refuse to participate in the survey were called in this seventh round. 18 households were excluded from the sample as they refused to participate in Round 6, and 21 were excluded as they weren’t contacted in the past three consecutive rounds. 1994 households (98.13 percent of the 2,032 attempted) were contacted and 1,979 (97.39 percent) were successfully interviewed. 13 households refused outright to be interviewed. For the sake of simplicity, this note focuses on modules related to mental health, employment dynamics, and social protection.